Ten years of the Riester pension scheme: No reason to celebrate - Kornelia Hagen; Axel Kleinlein (DIW Economic Bulletin, 2012)
Since their introduction, the Riester pension scheme and the individual Riester products have become less beneficial to savers. Contracts concluded today will often lead to lower returns compared to contracts concluded in 2001. From a social perspective, meaning pension benefits in relation to individual saving contributions plus state subsidy, overall returns on all insurance-based products are very low. This is due to the general decline in returns on the capital market and, in particular, to a series of government-mandated certification and calculation rules. Urgently needed structural reforms include the abolition of exchange costs, standardized cost information, certification with regards to content instead of formal certification and the regulation of calculation methods. In addition, limiting the number of products is also recommended. Given the shortcomings of the Riester system, there is good reason to fundamentally rethink old-age pension provision policy. In doing so, a targeted reduction or even elimination of extra public funding ought not to be taboo. The tax saved could be used to strengthen the pay-as-you-go state pension scheme.
Keywords: D18; D82; D91; E21; H55; 330; private pension provision; Riester scheme; funding principle; welfare state